Malaysian young women preference of local and foreign cosmetic brands - Kok, Yi Jing; Yap, Qian Yi (2019)
Cosmetic industry has experienced tremendous growth in recent years as the demand for cosmetics is increasing. With globalization and technology advancement, foreign cosmetic brands become increasingly popular and local cosmetic firms in Malaysia could possibly be affected by this trend negatively. Therefore, it is important for local cosmetic firms to pay attention and take note of the factors affecting consumers’ brand preferences. For this research, nine independent variables are being identified and investigated as the factors that will affect Malaysian young women’s cosmetic brand preferences. In this research, the researchers made use of nonprobability sampling techniques to collect data from target respondents. The target respondents are those young women aged between 18 and 35 years old. The sampling location is not limited to certain geographical location, but the researchers obtained most respondents from Klang Valley. Total 300 sets of questionnaires were successfully collected from target respondents. Primary data, such as questionnaire and secondary data, such as various journals and articles, were used to provide more accurate data for this research. By using SPSS version 19, researchers are able to analyze data and generate results for descriptive analysis, reliability test and inferential analysis. Lastly, the limitations of this research and the recommendations to enhance future research have been discussed in the last part.